Mali - The Demographic Challenge - World Bank (World Bank, 2012)
Mali has demographic characteristics similar to most sub-Saharan African countries, except for those of Southern Africa. The population of Mali is very young: in 1998, 46.3 percent of the population was under 15 years of age. Whereas mortality, especially infant and child mortality, has decreased rapidly, fertility has remained high over the past decades, equaling 6.6 children per woman on average. As a result, the rate of demographic growth has increased significantly over the last decades. Today, the natural population growth rate is estimated at 3.3 percent per year (it will take 21 years for the population to double). International migration somewhat slows down this growth, and the net population growth rate is estimated at 3 percent per year, which leads to a doubling of the population in 23 years. This study is presented in three chapters. The first chapter shows the present situation of the population of Mali and its prospects for the future. This chapter evaluates available demographic data, analyzes the size, geographic distribution as well as the structure and rate of growth of the population, including international migrations. It also presents population projections for the years 2005 to 2035, based on slow or rapid fertility decline scenarios. Chapter two is dedicated to the future implications of these demographic trends. It first addresses the development of human capital (demographic investment), especially in education and health. It then examines the macro-economic consequences of demographic growth for Mali. Finally, it briefly analyzes other consequences of the high population growth, in terms of increasing population density, agriculture, nutrition, urbanization, environmental degradation, and maternal and child health. The last chapter assesses the population policies in Mali and what is needed to set into motion a decline in fertility and presents practical recommendations.